INFLUENCE OF INFRASTRUCTURE , CONDITIONS PLACE WORK AND ATMOSPHERE WORK TO SATISFACTION EMPLOYEE WORK AND PERFORMANCE AT THE PERSONNEL AND DEVELOPMENT AGENCY HUMAN RESOURCES SOUTH BARITO REGENCY - Yusma Erwandi; Noor Ritawaty (Sean Institute, 2020)
This research aims to analyze the influence of infrastructure, workplace conditions and work atmosphere on employee performance by job satisfaction. This quantitative research uses intervening variables. Respondents in the research were 41 people using saturated sample technique. This research uses data collection method by questionnaire, interview and direct observation. The method of analysis used in this research is using descriptive and path analysis by Smart PLS version 3.3.2. The results of this research indicated direct influences are (1) infrastructure has positive correlation and significant influence to job satisfaction; (2) workplace conditions have positive correlation and significant influence to job satisfaction; (3) work atmosphere has positive correlation and significant influence to job satisfaction; (4) infrastructure has positive correlation and significant influence to employee performance; (5) workplace condition uncorrelation significantly influences employee performance; (6) work atmosphere uncorrelation has a significant influence on employee performance; (7) job satisfaction has positive correlation and significant influence to employee performance. Meanwhile indirect influences are: (1) infrastructure uncorrelation significantly influences employee performance by job satisfaction; (2) workplace conditions have positive correlation and significant influence to employee performance by job satisfaction; (3) work atmosphere has positive correlation and significant influence to employee performance by job satisfaction in personnel and human resources development agency of South Barito.